Analisis Risiko Bahaya K3 pada Pekerjaan Fasilitasi Tera/Tera Ulang dan Reparasi Timbangan Bukan Otomatis Mekanik (TBOM) Menggunakan Metode JSA dan HIRARC : Studi Kasus FTTU pada BSML Regional IV - Regina Ramadhania; Takdir Alisyahbana; Taufik Nur (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
Legal metrology has the role of providing assurance of the correctness of measurement results and legal certainty in the process of trade transactions that use Measuring, Measuring, Weighing, and Equipment (UTTP) tools for determining quantities as a basis for determining the price of goods and services. The implementation of legal metrology activities to ensure the correctness of measurement results is regulated in Law Number 2 of 1981 concerning Legal Metrology which aims to protect the public interest / consumers through guaranteeing the correctness of measurement results as well as order and legal certainty in the use of units of measure, unit standards, measurement methods and measuring, measuring, weighing and weighing equipment. Therefore, a study was conducted entitled Risk Analysis of OHS Hazards in the Facilitation of Tera / Retest Work and Repair of Mechanical Non-Automatic Scales (TBOM) Using the JSA and HIRARC Methods with a case study of the Tera Tera Retest Facilitation work at BSML Regional IV. Testing is done manually using scales up to 150 kg to ensure the correctness of the measurements. With the high risk experienced in testing and repair, risk mitigation is carried out with the HIRARC method with the results of 3 Medium Risk (medium risk) down to none, as well as 5 Low Risk (light risk) to 11 Very Low Risk to 11 risks from the initial 6 risks in the Tera Tera Re-facilitation of the Tera Session in the Market.